(untitled) (Wire Insights: Journal of Innovation Insights, 2023)
The article explains in detail the psychological characteristic of emotional intelligence and its development. The meaning of emotional intelligence is analysed and different concepts are theorized by a number of foreign scientists. The issues of stages of development of emotional intelligence and its different types are considered.